A stranger's game [large type] - Coble, Colleen (Thorndike Press large print Christian fiction., 2022)
"Even though Torie Bergstrom hasn't been back to Georgia since she was ten, she's happy to arrange a job for her best friend at one of the family properties on Jekyll Island. But when Torie learns that her best friend has drowned, she knows it is more than a tragic accident: Lisbeth was terrified of water and wouldn't have gone swimming by choice. Torie goes to the hotel under an alias, desperate to find answers. When she meets Joe Abbott and his daughter rescuing baby turtles, she finds a tentative ally. The more Torie and Joe dig, the more elusive the truth seems. One thing is clear: someone will risk anything-even more murder-to keep their secrets buried"--